2023
DOI: 10.1182/blood.2022018665
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged response after TPO-RA discontinuation in primary ITP: results of a prospective multicenter study

Abstract: Sustained response off-treatment (SROT) after thrombopoietin receptor agonist (TPO-RA) discontinuation has been reported in ITP. This prospective multicenter interventional study enrolled adults with persistent or chronic primary ITP and complete response on TPO-RAs. The primary endpoint was the proportion of patients achieving SROT (platelet count > 30x109/L and no bleeding) at W24 with no other ITP-specific medications. Secondary endpoints included the proportion of sustained complete response off-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…These findings are consistent with those of other published studies of eltrombopag and romiplostim, which report SRoT in up to around one‐third of patients 8,9,11 . Results from a previously reported prospective Phase II clinical trial investigating the activity of eltrombopag in adult patients with ndITP or pITP after first‐line therapy showed that the proportion of patients achieving SRoT for at least 6 months was 25% (13/51 patients) 9 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings are consistent with those of other published studies of eltrombopag and romiplostim, which report SRoT in up to around one‐third of patients 8,9,11 . Results from a previously reported prospective Phase II clinical trial investigating the activity of eltrombopag in adult patients with ndITP or pITP after first‐line therapy showed that the proportion of patients achieving SRoT for at least 6 months was 25% (13/51 patients) 9 .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with those of other published studies of eltrombopag and romiplostim, which report SRoT in up to around one-third of patients. 8,9,11 Results from a previously reported prospective Phase II clinical trial investigating the activity of eltrombopag in adult patients with ndITP or pITP after first-line therapy showed that the proportion of patients achieving SRoT for at least 6 months was 25% (13/51 patients). 9 SRoT in this case was defined as a platelet count of ≥30 Â 10 9 /L and at least a 2-fold increase from baseline count at the end of treatment (Week 24), tapering and discontinuation (up to Week 32) of eltrombopag, and subsequent maintenance of response in the absence of bleeding and rescue therapy (an additional 24 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations